Edukasi Kesehatan pada Lansia dengan Diabetes Melitus di Rumah Perawatan Althaf Kota Jambi - Dwi Yunita Rahmadhani; Rino M.; Jufri Al Fajri (Jurnal Abdimas Kesehatan (JAK), 2023)
Diabetes Mellitus is a group of heterogeneous disorders that marked with glucose level in the blood or usually called hiperglikemia. Most of mellitus patient did not check their glucose level unless there’s some symptoms that made them felt uncomfortable. The worse a person control their blood sugar, the more vulnerable they are to get a complication. There are several steps that could help to achieve a fully healthy condition, such as controlling lifestyle, eating habits, resting period, and exercise as suggested by health workers. Therefore, the community service activities targeted to improving elders concerns about diabetes mellitus. This activity held on December 2020 to January 2021 at Rumah Perawatan Al-Thaf Jambi. The object for this activity is elders that come to visit Rumah Perawatan Al-Thaf Jambi. In total, there were 10 Elders. All elders that participated in this activity able to follow the Educational learning events from beginning until the end of the session so that they can get the maximum results. This activity outputs is the increase of elders’ health quality so that they can live healthily and independently.